Psychoeducation Based on Short Education Movie as An Educational Media to Improve Knowledge about Online Game Addiction in Students - Nelma Liklikwatil; Floria Veramaya Imlabla; Paramita Kurnia Wiguna; Ummul Hariat; Nur Aisah Latuconsina; Agustiningsih Agustiningsih; Norra Hendarni Wijaya; Bety Agustina Rahayu (GLOBAL HEALTH SCIENCE GROUP, 2025)
Game addiction can result in a significant decrease in an individual's ability to perform routine activities. Lack of education about game addiction can cause behavioral disorders and other health problems. Seeing the existing problems, the purpose of this study is to conduct a psychoeducational analysis study based on short education movies as an educational medium to increase knowledge about online game addiction in students. This study is a quantitative study with a quasi-experimental pretest-protest design. This study will be conducted at Ambon vocational high schools. Sampling using random sampling techniques obtained 40 students. The statistical test used is the Wilcoxon signed Rank test. The results showed that the majority of respondents were 15 years old (57.5%) with the largest gender being female (62.5%). The majority of respondents had insufficient knowledge before being given psychoeducation based on short education movies as an educational medium to increase knowledge about online game addiction in students in Ambon city as many as 27 respondents (67.5%). The results of student knowledge after psychoeducation based on short education movies as an educational medium to increase knowledge about online game addiction in students in Ambon city are mostly in the good category, namely 30 respondents (75%). The results of the Analysis test obtained a p-Value of 0.001. The conclusion in this study is that there is a significant influence between psychoeducation based on short education movies as an educational medium to increase knowledge about online game addiction in students (p-value 0.001).